Aquaporin-1 Expression in Proliferative Vitreoretinopathy and in Epiretinal Membranes - Elie Motulsky (The Scientific World Journal, 2014)
Purpose. Aquaporin-1 (AQP1) is involved in cell migration and proliferation; therefore, the purpose of the study was to investigate its expression in proliferative vitreoretinopathy (PVR) and epiretinal membranes (ERM). Methods. 19 membranes from PVR and ERM were collected following eye surgery. AQP1 mRNA and protein expressions were determined by RT-qPCR and immunofluorescence in the membranes from PVR and ERM. Results. AQP1 mRNA and protein were expressed in both PVR and ERM as shown by RT-qPCR and immunofluorescence. AQP1 protein expression was heterogeneous among and between PVR and ERM and colocalized with alpha-smooth muscle actin (αSMA) and with glial fibrillary acidic protein (GFAP). There were a higher percentage of cells coexpressing AQP1 and αSMA than AQP1 and GFAP. GFAP and αSMA did not colocalize. Conclusion. Our data show for the first time AQP1 expression in both PVR and ERM. AQP1 is expressed mostly by the αSMA-positive cells, presumably myofibroblasts, but also by GFAP-positive cells, assumed to be glial cells. These original findings warrant further functional investigations aiming at studying the potential role of AQP1 in cell migration and proliferation occurring during the development of PVR and ERM.